Morphological lymphocytic reaction, patient prognosis and PD‐1 expression after surgical resection for oesophageal cancer. Issue 10 (15th August 2019) - Baba, Y.; Yagi, T.; Kosumi, K.; Okadome, K.; Nomoto, D.; Eto, K.; Hiyoshi, Y.; Nagai, Y.; Ishimoto, T.; Iwatsuki, M.; Iwagami, S.; Miyamoto, Y.; et al.
Abstract : Background: Immune checkpoint inhibitors, such as antibody against programmed cell death protein (PD‐1), have demonstrated antitumour effects in patients with malignancies, including oesophageal cancer. A lymphocytic reaction observed by pathological examination is a manifestation of the host immune response to tumour cells. It was hypothesized that a stronger lymphocytic reaction to tumours might be associated with favourable prognosis in oesophageal cancer. Methods: Using a database of resected oesophageal cancers, four morphological components of lymphocytic reactions (peritumoral, intranest, lymphoid and stromal) to tumours were evaluated in relation to clinical outcome, PD‐1 expression by immunohistochemistry and total lymphocyte count in blood. Results: Resected oesophageal cancer specimens from 436 patients were included in the study. Among the four morphological components, only peritumoral reaction was associated with patient prognosis (multivariable P for trend <0·001); patients with a higher peritumoral reaction had significantly longer overall survival than those with a lower reaction (multivariable hazard ratio 0·48, 95 per cent c.i. 0·34 to 0·67). The prognostic effect of peritumoral reaction was not significantly modified by other clinical variables (all P for interaction >0·050). Peritumoral reaction was associated with total lymphocyte count in the blood ( P < 0·001), supporting the relationship between local immune response and systemic immune competence. In addition, higher morphological peritumoral reaction was associated with high PD‐1 expression on lymphocytes in tumours ( P = 0·034). Conclusion: These findings should help to improve risk‐adapted therapeutic strategies and help stratify patients in the future clinical setting of immunotherapy for oesophageal cancer. Abstract : Among four components of lymphocytic reactions, only peritumoral reaction was associated with patient prognosis in 436 patients with oesophageal cancer, suggesting higher peritumoral reaction as a prognostic marker. Peritumoral reaction was associated with total lymphocytes in the blood and programmed cell death protein 1 (PD‐1) expression on lymphocytes in tumours. Will guide future immunotherapy Abstract : Antecedentes: Los inhibidores de los puntos de control inmunitario ( checkpoints ) (p.ej. los anticuerpos anti‐PD‐1) han demostrado efectos antitumorales en pacientes con tumores malignos, incluido el cáncer de esófago. La reacción linfocítica detectada en estudios anatomopatológicos es una manifestación de la respuesta inmune del huésped a las células tumorales. Se estableció la hipótesis de que una mayor reacción linfocítica a los tumores podría asociarse con un mejor pronóstico en el cáncer de esófago. Métodos: Usando una base de datos de 436 cánceres de esófago resecados, se evaluaron cuatro componentes morfológicos (peritumoral, intra‐epitelial, linfoide y estromal) de las reacciones linfocíticas a tumores en relación con los resultados clínicos, la expresión inmunohistoquímica de PD‐1 y el recuento total de linfocitos en sangre. Resultados: De los cuatro componentes, solamente la reacción peritumoral se asoció con el pronóstico del paciente ( P multivariable para tendencia < 0, 001): los pacientes con mayor reacción peritumoral presentaron una supervivencia global significativamente más prolongada que aquellos pacientes con menor reacción peritumoral (cociente de riesgos instantáneos multivariable, hazard ratio, HR: 0, 48; i.c. del 95%: 0, 34 –0, 67; P <0, 001). El efecto pronóstico de la reacción peritumoral no se modificó significativamente por otras variables clínicas (todas las P para la interacción > 0, 05). La reacción peritumoral se asoció con el recuento total de linfocitos en la sangre ( P < 0, 001), lo que respalda la relación entre la respuesta inmune local y la competencia inmune sistémica. Además, una elevada reacción morfológica peritumoral se asoció con una alta expresión de PD‐1 en linfocitos tumorales ( P = 0, 034). Conclusión: Estos hallazgos deberían ayudar a mejorar las estrategias terapéuticas adaptadas al riesgo y contribuir a estratificar a los pacientes en el entorno clínico futuro de la inmunoterapia para los pacientes con cáncer de esófago.